Self-Management and its Relation to Organizational Excellence - ABD ALL GHAL, BATOOL; MIRI HABEEB, LIQAA; DEKHN HAMZAH, KHITAM (International Journal of Engineering and Technology, 2018)
The immense competition in organizations turns the business into huge innovation war. Every organization is searching for ways to achieve organizational excellence to better serve their consumers and survive in this competitive era. Employees are considered main source of innovation and excellence in any organization.Â Therefore, this study focuses on the employee self-management practices to explain its role in organizational excellence. Self-management of employees makes them more dedicated, vigorous and engaged them in their work. The results of this study explain that self-management of employees contributes in organizational success in a positive way. Findings of this study contribute existing literature on this missing link between self-management and organizational excellence.